Upaya Meningkatkan Aktivitas dan Hasil Belajar Kimia dengan Pendekatan Contextual Teaching Learning di Kelas X SMAN 7 Rejang Lebong - Herlina Herlina (PendIPA Journal of Science Education, 2020)
The aims of this research were to determine the effectiveness learning methods with a contextual teaching learning (CTL) approach to increase the activity and student learning outcomes in redox reaction material in class X.1 of Rejang Lebong 7 Public High School. The research activity was carried out in two cycles, namely cycle I and cycle II. In the first cycle, the teacher had implemented a CTL approach which obtained student learning outcomes with average value of 68.39% and student learning completeness 67.74%. Out of 31 students who took the test, there were 21 students who completed learning. The activity of students in the first cycle has increased from pre-cycle, which is 56.69 or quite active category. Although activities and student learning outcomes from pre-cycle to cycle I began to increase, but have not reached the expected indicators. Therefore, the action continued to cycle II, where the student learning outcomes averaged 75.10 and classical learning completeness 87.10%. Likewise, the activity of students in the second cycle also increased, namely 71.53% or active category. From the results, it can be concluded that the use of learning methods with CTL approach can improve the activities and student learning outcomes in redox reaction material.